GST in India: reflections from food and agriculture - Naveen P Singh; Jaiprakash Bisen; Venkatesh P; Aditya K S (Agricultural Economics Research Review, 2023)
Goods and services tax or GST is an important fiscal instrument to ensure efficient, equitable and sustainable economic growth. India switched over to GST in 2017, bringing all economic activities, including those related to agricultural sector, under its ambit. Most agricultural services remain exempted from GST, and tax rates on several inputs and commodities have been reduced. Tax rates on machines and equipment used in dairy industry have marginally been reduced, while dairy products have been brought under tax net. Tax incidence machines and equipments used in agro-processing has increased. These changes in tax rates are likely to influence prices of inputs and their usage; adoption of technologies and prices of agricultural commodities and thereby farm profits. In this paper, we have attempted to highlight likely impacts of GST on input prices and cost of cultivation of important crops.